Research of problems and prospects of development of public control in the information and communication space - D. A. Okolyshev (Вестник университета)
The article is devoted to the study of problems and prospects of public control development in the information and communication space. An overview of studies in the interdisciplinary field of knowledge that are dedicated to potential threats in public political discourse affecting the consciousness of social groups is provided. The degree of elaboration regarding the issues facing the implementation of public control processes in the public administration system is assessed. The main issues facing the implementation of public control in information and communication networks are identified. It is substantiated that in the long term, intelligent systems will become a fundamental part of the communication flows analysis system. Based on the research conducted, a model of public control has been developed and tested in relation to the results of monitoring the provision of quality education. The study has established the strategic importance and advantage of using intelligent semantic analysis systems for the implementation of public control. It has been identified that fabricated information is not influenced by territorial affiliation. The object for which manipulation is intended and the target that affects the object by direct or indirect means, depending on the influence factors and the current socio-economic situation of the target subjects, are of primary importance. The author stresses that the study of specifics of the implementation of state policy in the public control system in conjunction with the assessment of municipal specifics is relevant and will serve further implementation of a decentralized system of public control. Based on the results of the study, a conclusion is made about the potential role of the state in the information and communication environment in the following years.